Bt cotton area contraction drives regional pest resurgence, crop loss, and pesticide use - Lu, Yanhui; Wyckhuys, Kris A.G.; Yang, Long; Liu, Bing; Zeng, Juan; Jiang, Yuying; Desneux, Nicolas; Zhang, Wei; Wu, Kongming (Wiley, 2022)
Genetically-modified crops expressing Bacillus thuringiensis (Bt) proteins have been widely cultivated, permitting an effective non-chemical control of major agricultural pests. While their establishment can enable an area-wide suppression of polyphagous herbivores, no information is available on the impact of Bt crop abandonment in entire landscape matrices. Here, we detail a resurgence of the cosmopolitan bollworm Helicoverpa armigera following a contraction of Bt cotton area in dynamic agro-landscapes over 2007–2019 in North China Plain. An 80% reduction in Bt cotton was mirrored in a 1.9-fold increase of ambient H. armigera population levels, culminating in 1.5–2.1-fold higher yield loss and a 2.0–4.4-fold increase in pesticide use frequency in non-Bt crops (i.e. maize, peanut, soybean). Our work unveils the fate of herbivorous insect populations following a progressive dis-use of insecticidal crop cultivars, and hints at how tactically deployed Bt crops could be paired with agro-ecological measures to mitigate the environmental footprint of crop production.